THE EFFECT OF USING INTERACTIVE GUESSING GAME TECHNIQUE ON FLUENCY STUDENT’S SPEAKING SKILL - Zully Zulaikho Puspitasari; slamet Asari (Universitas Muhammadiyah Gresik, 2018)
This article explains the result of research that aim to test whether usinginteractive guessing game technique give significant effect on fluency student’s speakingskill in short functional text of MTs. Bustanul Ulum Tanggungprigel. This research uses aquasi experimental research design. The population of this research was the VIII gradestudents of MTs. Bustanul Ulum Tanggungprigel. There were two classess that totalized50 students. The sample of this research was VIII A and VIII B. The sample was selectedby population sampling technique. The instruments were speaking test. The data wereanalyzed by independent sample t-test formula. The result of this research were theimplementation of using interactive guessing game was significant to improve fluencystudent’s speaking skill. It can be conclude that interactive guessing game technique gavesignificant effect toward fluecny student’s speaking skill at MTs. Bustanul UlumTanggungprigel.